THERAPEUTIC PRACTICES AND ISLAMIC SPIRITUALITY IN THE MODERN CONTEXT: A STUDY OF THE MUSLIM THERAPISTS’ COMMUNITY IN SIMPANG SELAYANG, MEDAN - Siti Nur Cahayati; Ismail (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
This study analyzes the implementation of holistic therapy grounded in Islamic spirituality by the Terapis Muslim community in Simpang Selayang, Medan, and examines the meaning and functions of Islamic spirituality within therapeutic practices as a response to the needs of modern society. A qualitative approach is employed from the perspective of the sociology of religion. Data collection methods include observation, in-depth interviews, and documentation involving the community founder, therapists, therapy trainees, and patients. The findings indicate that holistic therapy is implemented through the integration of physical, mental, emotional, and spiritual dimensions using various therapeutic modalities, such as hijama (cupping therapy), mental therapy, ruqyah (Islamic spiritual healing), and back reflexology (sipung). Islamic spirituality is conceptualized as an awareness of the relationship between human beings and Allah, expressed through the values of ikhlas (sincerity), sabr (patience), shukr (gratitude), and tawakkul (reliance upon Allah). Within therapeutic practice, spirituality functions as a source of meaning in life, a coping mechanism for addressing the pressures of modern life, and a means of promoting behavioral and social transformation. Drawing upon the perspectives of Symbolic Interactionism and the Theory of Religiosity, the findings demonstrate that holistic therapy grounded in Islamic spirituality serves not only as a healing intervention but also as a process of meaning-making and the strengthening of religiosity in contemporary society.